2018
DOI: 10.1016/j.jenvp.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Restoration, well-being, and everyday physical activity in indoor, built outdoor and natural outdoor settings

Abstract: Physical activity in natural settings has been found in experimental research to be more restorative than physical activity in built indoor or outdoor settings, yet we lack evidence of this in everyday life. In this study we examined recalled restoration (with the 9-item Restoration Outcome Scale) of the most recent physical activity session in indoor, built outdoor and natural outdoor settings using measurement invariance tests (n=2577). We also compared the relationships between restoration, emotional well-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…In addition to explanations posited elsewhere (e.g., that nature exposure restricts negative appearance-related cognitions and provides spaces to critically appraise unhealthy appearance ideals; , we conjecture that repeated nature exposure provides recurrent opportunities for restoration that accumulate over time into more positive body image (see Pasanen, Ojala, Tyrväinen, & Korpela, 2018). That is, experiencing the restorative effects of nature likely supports the promotion and maintenance of more positive body experiences and activities in the long term.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition to explanations posited elsewhere (e.g., that nature exposure restricts negative appearance-related cognitions and provides spaces to critically appraise unhealthy appearance ideals; , we conjecture that repeated nature exposure provides recurrent opportunities for restoration that accumulate over time into more positive body image (see Pasanen, Ojala, Tyrväinen, & Korpela, 2018). That is, experiencing the restorative effects of nature likely supports the promotion and maintenance of more positive body experiences and activities in the long term.…”
Section: Discussionmentioning
confidence: 56%
“…For example, a recent meta-analysis reported that there was a positive relationship between trait mindfulness and connectedness to nature (weighted effect size of r = 0.25; Schutte & Malouff, 2018). Other neglected variables that may be worth incorporating into future studies include measures of recurrent or perceived restorative experiences in natural environments (Pasanen et al, 2018) and positive impact (McAllister, Bhullar, & Schutte, 2017). Putting together these variables alongside the variables included in the present work would allow for more complex modelling and a fuller understanding of direct and mediational pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, future studies may benefit from more complex modelling that includes a wider range of variables. Such variables could include those that have been previously found to mediate relationships between nature exposure and positive body image, such as self-compassion (see Swami et al, 2019), as well as possibly relevant factors, including engagement with natural beauty (Diessner, Solom, Frost, Parsons, & Davidson, 2010) and recurrent or perceived restorative experiences in natural environments (Pasanen, Ojala, Tyrväinen, & Korpela, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The MMS score for depression and State-Trait Anxiety Inventory (STAI) [25] score were also lower on the forest days [26]. The psychological responses were also measured by the profile of mood states (POMS) [7,9,27], Zuckerman inventory of personal reactions (ZIPPERS) [28], restorative outcome scales (ROS) [29,30,31], subjective vitality scale (SVS) [32], and positive and negative affect schedule (PANAS) [33,34]. All indicators showed that the forest setting has more positive psychological restorative effects than the urban setting.…”
Section: Introductionmentioning
confidence: 99%